Sharing out the land of the Northumbrians: exploring place-names and township boundaries (part three) - Wrathmell, Stuart (Medieval Settlement Research, 2022)
Much of the debate about Scandinavian settlement in England has traditionally focused on its chronology, and on the number of people involved: when and how many? There are, though, other arguably more interesting and illuminating questions about the settlement: where did it take place, how was it implemented and who planned it? Any attempt to answer these last three questions will, of course, have implications for our understanding of the first two. The earlier articles in this series explored the patterning of settlement evidenced through the mapping of township territories associated with place-names ending in Old Norse (ON) -bý, and analysing the ways in which these townships interplayed with neighbouring communities marked by place-names with Old English (OE) generics, notably those in -tūn (Wrathmell 2020; 2021). They rested (as this third article rests) on two underlying hypotheses. The first is that many townships in eastern Yorkshire with OE place-names were already in existence at the time of the Scandinavian settlement, and retained their names beyond the period of settlement – though some of them, perhaps for various reasons, acquired ON specifics including personal names. The second is that townships with generics in ON were created as territories for some groups of Scandinavian settlers – though not necessarily for all of them. This concluding article attempts, first, to draw out some broad themes from the analyses offered in the earlier articles, exploring intentions, means of implementation and actors in the Scandinavian settlement. In further case studies, focusing on the archiepiscopal soke estates of Helperby and Weaverthorpe, and on places in the study area with ‘Kirby’ names (see Fig. 1), it then attempts to trace the role that the Church, specifically the archbishops of York, may have played in managing both the settlement and the subsequent Christianisation of the newly settled communities. The final sections consider the chronology of settlement, and the circumstances that would have promoted or discouraged the persistence of earlier township names during and beyond the Scandinavian settlement. As with the previous articles, the case studies, and therefore the conclusions, are limited to parts of the former Deiran kingdom in southern Northumbria.